2018
DOI: 10.1371/journal.pone.0207606
|View full text |Cite
|
Sign up to set email alerts
|

Predominance and high diversity of genes associated to denitrification in metagenomes of subantarctic coastal sediments exposed to urban pollution

Abstract: The aim of this work was to characterize the microbial nitrogen cycling potential in sediments from Ushuaia Bay, a subantarctic environment that has suffered a recent explosive demographic growth. Subtidal sediment samples were retrieved in triplicate from two urban points in the Bay, and analyzed through metagenomic shotgun sequencing. Sequences assigned to genes related to nitrification, nitrate reduction and denitrification were predominant in this environment with respect to metagenomes from other environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…In addition, Prokka and FeGenie annotations were used in combination to search for MAGs having genetic potential for both iron oxidation (cyc2 and MtoA genes) and denitrification or DNRA. NosZ genes were also specifically classified into clade I and clade II using blastP and a custom database consisting of deduced amino acid sequences of nosZ genes from a previously published phylogenetic tree (Altschul et al, 1990(Altschul et al, , 1997Calderoli et al, 2018).…”
Section: Bioinformatic Analysis Of Shotgun Metagenomic Datamentioning
confidence: 99%
“…In addition, Prokka and FeGenie annotations were used in combination to search for MAGs having genetic potential for both iron oxidation (cyc2 and MtoA genes) and denitrification or DNRA. NosZ genes were also specifically classified into clade I and clade II using blastP and a custom database consisting of deduced amino acid sequences of nosZ genes from a previously published phylogenetic tree (Altschul et al, 1990(Altschul et al, , 1997Calderoli et al, 2018).…”
Section: Bioinformatic Analysis Of Shotgun Metagenomic Datamentioning
confidence: 99%
“…Several months after the DWH (Deepwater Horizon) spill, the sediment of the wellhead area region was enriched with Chloroflexi , Firmicutes , Methylotrophic , and Actinobacteria [ 47 ]. An exploratory survey was conducted and showed that—after a decade—the microorganisms of the sediments had returned to pre-spill composition [ 10 ].…”
Section: Microorganisms Involved In the Removal Of Oil Spills From Ma...mentioning
confidence: 99%
“…The presence of these respiratory chains in saline and osmolyte conditions leads to intracellular agglomeration of piezolytes along with ectoine agglomeration [ 127 ], N-trimethylamine oxide (TMAO) [ 128 ], and β-hydroxybutyrate [ 142 ]. In Alcanivorax borkumensis , under saline and osmolyte conditions, gene upregulation and intracellular ectoine accumulation were related to increased culture activity, diminished cell damage, and higher cell numbers [ 10 , 143 ].…”
Section: Factors Engaged In Microbial Degradationmentioning
confidence: 99%
“…Metagenomic surveys have identified DNR-associated genes in both soil and hypolithic (under rock) samples from MDV ( Chan et al, 2013 ; Wei et al, 2016 ), but with limited information on the genetic diversity or environmental variables determining the presence of DNR genes. Another study used the marker gene nirG for nitrate reduction ( Jung et al, 2011 ), which may hint the presence of DNR in MDV ( Calderoli et al, 2018 ), although its biogeochemical drivers are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that the multiple nitrogen-cycling pathways in MDV are near the limits of their distribution and the strong physicochemical heterogeneity of MDV soils are the main selective forces that determine the complexity of the nitrogen metabolism in these environments. Here we used metagenomics and biogeochemical data of 32 MDV sites ( Lee et al, 2019 ; Figure 1 and Supplementary Table 1 ), to explore, with an unprecedented integral view, all nitrogen-cycling pathways, without the constraints of focusing on single genetic markers ( Calderoli et al, 2018 ; Ortiz et al, 2020 ). With this approach, we provide a detailed description of the relationships between the genes involved in the entire nitrogen-cycling and its relation with MDV spatial biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%